Proactive planning for contextual fit: the role of the implementation premortem - Guillermo M. Wippold; Kaylyn A. Garcia; Ariel Domlyn; Dylan Wong; Maria E. Fernandez (Implementation Science Communications)
Abstract Background Implementation failure is a major barrier to program success. It is widely acknowledged that context matters—individual, community, and organizational norms, values, environment, and priorities influence successful program implementation. A mismatch between how the program was intended to be delivered and the constraints of the context in which it was delivered is a major cause of implementation failure. The barriers to implementation are usually understood after a program has failed. Although there are tools that can help accommodate for, or overcome, contextually-driven sources of implementation failure, there remains a significant gap – a tool and structured approach to analyze data that is designed to proactively predict how and why implementation might fail due to context. Methods and Results This manuscript contains: (1) the history and underpinning theories behind the implementation premortem; (2) a description of the implementation premortem – a tool that can be used prospectively in conjunction with existing tools to proactively promote contextual fit of implementation strategies; (3) an example of an implementation premortem; (4) useful frameworks to use when analyzing data derived from an implementation premortem; and (5) challenges and limitations of the implementation premortem. Conclusions Ultimately, an implementation premortem is a tool that when combined with a structured analytic approach can be used to promote efficiency in learning about contextually-relevant considerations that can influence the impact, feasibility, and sustainability of an implementation effort.